The epidemiology, healthcare and societal burden of basal cell carcinoma in Wales 2000–2018: a retrospective nationwide analysis - Nader Ibrahim (British Journal of Dermatology, 2023)
BackgroundBasal Cell Carcinoma (BCC) represents the most commonly occurring cancer worldwide within the Caucasian population. Reports predict 298 308 cases of BCC in the UK by 2025, at a cost of £265-366 million to the National Health Service (NHS). Despite the morbidity, societal and healthcare pressures that manifest, routinely collected healthcare data and global registration remains limited.ObjectivesTo calculate the incidence of BCC in Wales between 2000-2018 and to establish the healthcare utilisation and estimated cost of care.MethodsThe Secure Anonymised Information Linkage (SAIL) Databank is one of the largest and most robust health and social care data repositories in the UK. Cancer registry data was linked to routinely collected healthcare databases between 2000-2018. Pathological data from Swansea Bay University Health Board (SBUHB) was used for internal validation.Results61,404 histologically proven BCC were identified during the study period within the SAIL databank. The European age standardised incidence (EASR) for BCC in 2018 was 224.6 per 100,000. Based on validated regional data a 45% greater incidence was noted within SBUHB pathology versus matched regions within SAIL between 2016-2018. A negative association between deprivation and incidence was noted with a higher incidence in the least socially deprived and rural dwellers. Approximately 2% travelled 25-50 miles for dermatological services in comparison to 37% for plastic surgery. Estimated NHS costs of surgically managed lesions 2002-2019 equated to £119.2-164.4 million.ConclusionRobust epidemiological data which are internationally comparable, and representative is scarce within non-melanoma skin cancer despite cases of individual improvement. The rising global incidence coupled with struggling healthcare systems in the post Covid-19 recovery period serves to intensify the societal and healthcare impact. This study is the first to demonstrate the incidence of BCC in Wales and one of a small number in the UK using internally validated large cohort datasets, and further demonstrates one of the highest published incidences within the UK and Europe. In the modern era of health informatics and advanced analytics it is imperative that we capitalise on routinely collected healthcare data. Therefore, it must be accurate, comprehensive, and accessible otherwise services will under-deliver.